2016
DOI: 10.1186/s13000-016-0509-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequent detection of human polyomavirus 6 in keratoacanthomas

Abstract: BackgroundThe recent discovery of the Merkel cell polyomavirus and its consistent association with Merkel cell carcinoma has drawn attention to the numerous recently discovered polyomaviruses and their possible involvement in the etiopathogenesis of non-melanoma skin cancer (NMSC). Data on the recently discovered human polyomavirus 6 (HPyV6) and its role in NMSC are sparse and in part controversial.MethodsIn the present study we tested a large number (n = 299) of NMSC specimens for the presence of human polyom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
0
34
2
1
Order By: Relevance
“…In their study, 42.3% of all 59 examined KA were positive for HPyV6 DNA tested by PCR, which also was confirmed with FISH hybridisation. Likewise, higher prevalence numbers of HPyV6 were also reported in basal cell carcinomas, squamous cell carcinomas and trichoblastomas 4. In contrast, in the present study, HPyV6 DNA was not detected in KA or SN.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In their study, 42.3% of all 59 examined KA were positive for HPyV6 DNA tested by PCR, which also was confirmed with FISH hybridisation. Likewise, higher prevalence numbers of HPyV6 were also reported in basal cell carcinomas, squamous cell carcinomas and trichoblastomas 4. In contrast, in the present study, HPyV6 DNA was not detected in KA or SN.…”
Section: Discussioncontrasting
confidence: 71%
“…Nevertheless, recently Beckervordersandforth et al 4 suggested a link between HPyV6 and KA. In their study, 42.3% of all 59 examined KA were positive for HPyV6 DNA tested by PCR, which also was confirmed with FISH hybridisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to HPyV7, HPyV6 has not yet been linked with specific skin disease. Low levels of HPyV6 DNA have been detected in several types of epithelial neoplasms and a contribution of HPyV6 to these neoplasms has not been excluded 10, 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Viral loads of HPyV6 tend to be much higher than those of HPyV7, with significantly higher viral burdens of both species found in individuals over 80 years of age . HPyV6 and HPyV7 can be detected using PCR on DNA extracted from skin scrapings or biopsies …”
Section: Human Polyomaviruses 6 Andmentioning
confidence: 99%